2012
DOI: 10.1007/978-3-642-30229-9_19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atomic Oxygen and Grease on Outgassing and Adhesion of Silicone Elastomers for Space Applications

Abstract: An investigation of silicone elastomers for seals used in docking and habitat systems for future space exploration vehicles is being conducted at NASA. For certain missions, NASA is considering androgynous docking systems where two vehicles each having a seal would be required to: dock for a period of time, seal effectively, and then separate with minimum push-off forces for undocking. Silicone materials are generally chosen for their wide operating temperatures and low leakage rates. However silicone material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Typically, small O-rings have been used for material screening tests to help select the final seal material for an application. 4,5 However, larger O-rings have also been tested as potential seal designs for various applications.…”
Section: O-ringsmentioning
confidence: 99%
“…Typically, small O-rings have been used for material screening tests to help select the final seal material for an application. 4,5 However, larger O-rings have also been tested as potential seal designs for various applications.…”
Section: O-ringsmentioning
confidence: 99%
“…This stickiness helps to make a good seal; however, can cause problems when spacecraft undock . There are several options to mitigate this unwanted adhesion such as targeted use of AO, radiation in the vacuum‐UV range <200 nm, and application of a suitable grease . The grease‐based sunscreens developed to block UV were also designed to control adhesion; thus another objective of the research presented here was to sufficiently lower seal adhesive forces with the application of a UV blocking sunscreen.…”
Section: Introductionmentioning
confidence: 99%
“…[7] While a concrete conclusion cannot be drawn from such a result, it is worth discussing as an observed trend.…”
Section: Control Tml% Ao Tml%mentioning
confidence: 93%
“…One study did show a relationship between AO and outgassing, as AO exposure was shown to slightly reduce outgassing of an O-ring. [7] It is possible to visualize all three mechanisms of outgassing being affected by AO. The breaking of bonds and oxidation that occurs on material surfaces due to AO could change the amount of material desorbed from the surface.…”
Section: Combined Atomic Oxygen and Outgas Testingmentioning
confidence: 99%
See 1 more Smart Citation